Thick Translation: A Conversation on Translating Indonesian Fiction - Michael Nieto Garcia (k@ta: A Biannual Publication on the Study of Languange and Literature, 2024)
This conversation on translation theory and practice with Michael Nieto Garcia and a mixed group of State University of New York (SUNY) students took place on 29 October 2019 at the Potsdam campus in New York State. The talk/interview was conducted by the invitation of Professor Richard M. Henry for his Literature and Translation Studies course (LITR520), and it was supported by the Dorf Yes fund at SUNY Potsdam. Some additions were made to the interview transcript to provide explanatory context and to articulate key points. A concluding thoughts section was added to summarize some translation takeaways.